Convective heat transfer of spring meltwater accelerates active layer phase change in Tibet permafrost areas - Y. Zhao; Z. Nan; Z. Nan; H. Ji; L. Zhao (The Cryosphere, 2022)
Convective heat transfer (CHT) is one of the important processes that control the near-ground surface heat transfer in permafrost areas. However, this process has often not been considered in most permafrost studies, and its influence on freezing–thawing processes in the active layer lacks quantitative investigation. The Simultaneous Heat and Water (SHAW) model, one of the few land surface models in which the CHT process is well incorporated into the soil heat–mass transport processes, was applied in this study to investigate the impacts of CHT on the thermal dynamics of the active layer at the Tanggula station, a typical permafrost site on the eastern Qinghai–Tibet Plateau with abundant meteorological and soil temperature and soil moisture observation data. A control experiment was carried out to quantify the changes in active layer temperature affected by vertical advection of liquid water. Three experimental setups were used: (1) the original SHAW model with full consideration of CHT, (2) a modified SHAW model that ignores CHT due to infiltration from the surface, and (3) a modified SHAW model that completely ignores CHT processes in the system. The results show that the CHT events occurred mainly during thaw periods in melted shallow (0–0.2 m) and intermediate (0.4–1.3 m) soil depths, and their impacts on soil temperature at shallow depths were significantly greater during spring melting periods than summer. The impact was minimal during freeze periods and in deep soil layers. During thaw periods, temperatures at the shallow and intermediate soil depths simulated under the scenario considering CHT were on average about 0.9 and 0.4 ∘C higher, respectively, than under the scenarios ignoring CHT. The ending dates of the zero-curtain effect were substantially advanced when CHT was considered due to its heating effect. However, the opposite cooling effect was also present but not as frequently as heating due to upward liquid fluxes and thermal differences between soil layers. In some periods, the advection flow from the cold layer reduced the shallow and intermediate depth temperatures by an average of about −1.0 and −0.4 ∘C, respectively. The overall annual effect of CHT due to liquid flux is to increase soil temperature in the active layer and favor thawing of frozen ground at the study site.